Effects of ouabain on vascular reactivity - Vassallo D.V.; E. Songu-Mize; L.V. Rossoni; S.M.C. Amaral (Brazilian Journal of Medical and Biological Research, 1997)
Ouabain is an endogenous substance occurring in the plasma in the nanomolar range, that has been proposed to increase vascular resistance and induce hypertension. This substance acts on the a-subunit of Na+,K+-ATPase inhibiting the Na+-pump activity. In the vascular smooth muscle this effect leads to intracellular Na+ accumulation that reduces the activity of the Na+/Ca2+ exchanger and to an increased vascular tone. It was also suggested that circulating ouabain, even in the nanomolar range, sensitizes the vascular smooth muscle to vasopressor substances. We tested the latter hypothesis by studying the effects of ouabain in the micromolar and nanomolar range on phenylephrine (PE)-evoked pressor responses. The experiments were performed in normotensive and hypertensive rats in vivo, under anesthesia, and in perfused rat tail vascular beds. The results showed that ouabain pretreatment increased the vasopressor responses to PE in vitro and in vivo. This sensitization after ouabain treatment was also observed in hypertensive animals which presented an enhanced vasopressor response to PE in comparison to normotensive animals. It is suggested that ouabain at nanomolar concentrations can sensitize vascular smooth muscle to vasopressor stimuli possibly contributing to increased tone in hypertension